Multilingual Data Management In Database Environment - Md. Latiful Hoque, Abu Sayed; Arefin, Mohammad Shamsul (Malaysian Journal of Computer Science, 2009)
Global E-Commerce and E-Governance programs have brought into sharp focus for the need of database systems to store and manipulate data efficiently in a suite of multiple languages. While existing database systems provide some means of storing and querying multilingual data, they suffer from redundancy proportional to the number of language support. In this paper, we propose a system for multilingual data management in distributed environment that stores data in information theoretic way in encoded form with minimum redundancy. Query operation can be performed from the encoded data only and the result is obtained by decompressing it using the corresponding language dictionaries for text data or without dictionary for other data. The system has been evaluated by both syntactic data and real data obtained from a real life schema. We have compared the performance of our system with existing systems. Our system outperformed the existing systems in terms of both space and time.